The Purchase Intentions Towards Functional Food: A Systematic Review of The Literature - Patcharapak SURIWONG; Inthawoot SUPPAVORASATIT; Thira CHAVARNAKUL (Communications of International Proceedings, 2023)
During the last few decades, social interest in functional food consumption and demands increased worldwide. Functional food is defined as a food product that is fortified with ingredients that have advantageous physiological effects of the food. Functional food is perceived as more nutritious and healthier than conventional food. The increase in demand can be explained by increasing concern about healthcare and the desire of old people to improve their quality of life. In this study, the main scope of the present review is focused on the factors affecting purchase intentions and willingness to pay for functional food based on systematic reviews of the literature in this field over the past two decades (2003-2023). The results show that the factors affecting purchase intentions could be classified into two categories: consumer-related and product-related factors.  Consumer-related factors are demographics, attitudes/perceptions/beliefs, subjective norms, health concerns and values. Product-related factors are product attributes, price and perceived quality. Most of the research about consumer-related factors had used Theory of Planned Behavior (TPB) as a primary theory to study consumer’s behavior in which attitudes, subjective norms and perceived behavioral control are determinants that influences consumer’s intention to do certain behavior. In the point of functional food, consumer’s perceptions and/or beliefs will influence their attitudes towards the functional food. Consequently, consumer’s attitudes towards functional food will directly or indirectly influence the intention to purchase. Consumer’s perceived behavioral control are income and self-efficacy. Meanwhile, the main product attributes that influence purchase intentions are base product, health claims and brand. Our findings also showed that the purchase intention from product-related factors was also influenced by perceived fit between base product and functional ingredient combinations. Providing health claims and information on the label could significantly increase purchase intention. In addition, effective branding increase consumer’s familiarity, resulting in an increase in purchase intention. However, price had a negative effect on consumer’s purchase intention, but this negative effect could be offset by health consciousness.
Keywords: Purchase intention; Willingness to Pay; Functional Food